De oude fotodokumentatie over Rwanda in het museum van Tervuren - Creemers-Palmers, Magda (Afrika Focus, 1992)
In september 1989 the 'Musée national du Rwanda' was inaugurated in Butare (Rwanda). Construction and arrangement of the Museum were completed by the 'Musée royal de l'Afrique centrale' of Tervuren. For this occasion, Tervuren started to collect an 'ancient' photo-documentation of Rwanda, to supply the new Rwanda-Museum with pictorial sources. Public as well as some private collections were gathered so that a final selection could be done. Up till now this photo-documentation is still kept in the Museum of Tervuren. For the sake of the historical research about Rwanda, our final purpose is, in co-operation with the Rwanda-Museum, to complete and to gather as much the photographic evidence as possible. Moreover, these sources need to be identified and described; only future and elaborated research will reveal more data about this important photographic documentation. KEY WORDS: African photo-history, photography, 'Musée national du Rwanda' (Butare), 'Musée royal de l'Afrique centrale'(Tervuren), photo-documentation, Rwanda